BS EN ISO 7668. Anodizing of aluminium and its alloys. Measurement of specular reflectance and specular gloss of anodic oxidation coatings at angles of 20 degrees, 45 degrees, 60 degrees or 85 degrees. (1st March 2021) - British Standards Institution,
No abstract available